2022
DOI: 10.1002/cnma.202100454
|View full text |Cite
|
Sign up to set email alerts
|

Fluorapatite‐Supported Palladium Catalyst for the Synthesis of Alkenyl Nitriles

Abstract: Fluorapatite-supported palladium catalyzed C=C bond cleavage of α, β-unsaturated ketones to alkenyl nitriles is presented. The reaction was performed with different basic catalysts, such as hydroxyapatite (HAP), fluorapatite (FAP), tert-butoxyapatite (TBAP), and MgÀ AlÀ HT derived oxide. Later, fluorapatite-supported palladium (PdFAP) catalyst was prepared by treatment of fluorapatite with bis(benzonitrile) palladium(II) chloride. PdFAP catalyst was characterized by XRD, TEM, BET, CHN analysis, ICP-AES and FTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Further peaks at the reflection of 25°, 26°, 29°, 30°, 38°, 40°, 41°, 46°, 49°, 50°, 51°, and 53°correspond to (229), (105), (350), (300), (100), (99), (95), (105), (106), (98), (97), and (101) (Figure 1). 22,34 The XRD peaks of FAP and metal-FAP (PdFAP, ZnFAP, and CuFAP) are found to be similar. The crystalline structure of pure FAP was not disturbed by the metal exchange.…”
Section: Catalyst Characterization Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Further peaks at the reflection of 25°, 26°, 29°, 30°, 38°, 40°, 41°, 46°, 49°, 50°, 51°, and 53°correspond to (229), (105), (350), (300), (100), (99), (95), (105), (106), (98), (97), and (101) (Figure 1). 22,34 The XRD peaks of FAP and metal-FAP (PdFAP, ZnFAP, and CuFAP) are found to be similar. The crystalline structure of pure FAP was not disturbed by the metal exchange.…”
Section: Catalyst Characterization Resultsmentioning
confidence: 93%
“…The FTIR spectra (Figure 2) of all catalysts show PO 4 vibrational frequencies similar to that reported in the literature. 22,34,36 Different vibrational PO 4 3− groups are obtained from FTIR spectra. The stretching of the phosphate group in symmetric and asymmetric modes is 962 cm −1 as the symmetric stretching mode ν 1 and ν 3 , whereas the asymmetric stretching mode is from the band 1093 cm −1 .…”
Section: Catalyst Characterization Resultsmentioning
confidence: 99%
“…They find applications in glass ceramics, bone therapeutic biomaterials, and coating of bone prosthesis. Recently, Kantam et al reported the application of fluorapatite in Henry’s reaction and also for the synthesis of alkenyl nitriles. , To explore fluorapatite further, we used FAP as a versatile catalyst for the WE reaction with a wide range of substrate scope. The present work deals with the comparison of FAP (fluorapatite), HAP (Hydroxyapatite), and TBAP (tert-butoxyapatite) catalysts in order to study the effect of basicity on the WE reaction.…”
Section: Introductionmentioning
confidence: 99%